(untitled) (SAARC Journal of Agriculture, 2015)
Moisture stress is a major constraint in productivity across the wheat growing zones of India. Climate change and uneven rainfall further aggravate the situation under moisture stress environments. Wheat genotypes capable of giving increased yield under a broad range of optimal and sub-optimal water availability are considered desirable. This study was undertaken to evaluate various selection indices of moisture stress and their applicability in identifying drought tolerant wheat genotypes which can adapt to various moisture stressed environments in different wheat growing zones of India i.e., North Western Plain Zone, North Eastern Plain Zone, Central Zone and Peninsular Zone. A set of wheat genotypes were tested under moisture stress condition of different irrigation regimes. Irrigation treatments were arranged as main plots and varieties as sub plots. Fifteen wheat varieties representing major wheat growing zones of India were tested for water stress tolerance during two consecutive years. It was found that yield under irrigated conditions (Ypi), yield under stress conditions (Ysi) and lower stress tolerance index (STI), were marked indices for stress tolerance. Significantly positive correlation of Ypi and Ysi with STI, mean productivity (MP), geometric mean productivity (GMP) were obtained during both the years of the study. The indices of STI, MP and GMP could be used as the desirable indices for screening drought tolerant varieties. On the basis of findings of these indices wheat varieties NI-5439, WH-1021 and HD-2733 were found having higher stress tolerance and with better yield potential under both normal and restricted irrigation conditions of India. SAARC J. Agri., 13(1): 148-161 (2015)